Unpacking and repacking gender-transformative research: Reflections from a method-design workshop - Bailey, Arwen; Begum, Khadija; Choudhury, Afrina; Ewell, Hanna; Farnworth, Catherine Rozel; Jiron Sosa, Jean Pierre; Mosbah, Menna; Osei-Amponsah, Charity; Rietveld, Anne (2024)
In the heart of Lima, a recent workshop on gender-transformative research methodologies (GTRM) was not your average academic gathering. For three days, this vibrant workshop was a hands-on, dynamic event focused on one mission: developing impactful methods for gender-transformative research for development.